2019
DOI: 10.1111/iju.14004
|View full text |Cite
|
Sign up to set email alerts
|

Association between tumor contact surface area and parenchymal volume change in robot‐assisted laparoscopic partial nephrectomy carried out using the enucleation technique

Abstract: Objective To evaluate the change in the operated parenchymal volume during robot‐assisted partial nephrectomy limited to the enucleation technique, and to analyze the predictors of decrease in operated parenchymal volume, including the tumor contact surface area. Methods The study included 135 patients who underwent robot‐assisted partial nephrectomy for T1 renal tumors using the enucleation technique. Measurements of the parenchymal volume, tumor volume and contact surface area were obtained in the venous pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…27 We believe it is now meaningless to set the threshold 30 min for T1b or RENAL nephrometry score ≥9 T1b tumors if methods to minimize normal renal parenchymal loss are to be applied. 28 In contrast, when stratified by different thresholds using propensity score matching, % eGFR decline was larger for the longer WIT than the shorter WIT group, with and without significance at the 20 and 25 min thresholds, respectively (data not shown). The eGFR difference in both was approximately 1.5-1.8 mL/min/1.73 m 2 , and seemed clinically negligible.…”
Section: Discussionmentioning
confidence: 87%
“…27 We believe it is now meaningless to set the threshold 30 min for T1b or RENAL nephrometry score ≥9 T1b tumors if methods to minimize normal renal parenchymal loss are to be applied. 28 In contrast, when stratified by different thresholds using propensity score matching, % eGFR decline was larger for the longer WIT than the shorter WIT group, with and without significance at the 20 and 25 min thresholds, respectively (data not shown). The eGFR difference in both was approximately 1.5-1.8 mL/min/1.73 m 2 , and seemed clinically negligible.…”
Section: Discussionmentioning
confidence: 87%
“…Large tumors tend to have larger contact surfaces on excision, which is associated with renal mass loss. 15 Moreover, according to our previous study, larger-diameter tumors (i.e., ‡30 mm) are highly likely to be surrounded by pseudocapsules. 27 In such tumors, enucleation is speculated to be easy and safe.…”
Section: Discussionmentioning
confidence: 88%
“…23 We previously reported that larger tumor contact surface area is associated with more parenchymal volume loss in RAPN. 15 As more vascularized renal parenchyma is likely to be included in tumors with high RNS (large diameter, hilar, and median polar location), a running suture for kidney reconstruction owes unavoidable risk of compromising intrarenal vascular anatomy. 24,25 Thus, it is reasonable to presume that efforts to preserve any little volume of parenchyma for these tumors are crucial to prevent acute kidney injury or CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this series, we performed RAPN with the same port place at the same site. Port placement for RAPN differs depending on the institution, surgeons' preference, type of da Vinci system (Si or Xi) used, or total number of ports including those of the assistants . Compared to Caucasian patients, Asian patients are slimmer and require narrower intra‐abdominal working space in general .…”
Section: Discussionmentioning
confidence: 99%